The Effect of Plasma Pretreatment and Cross-Linking Degree on the Physical and Antimicrobial Properties of Nisin-Coated PVA Films - Kolarova Raskova, Zuzana; Stahel, Pavel; Sedlarikova, Jana; Musilova, Lenka; Stupavska, Monika; Lehocky, Marian (Materials (Basel, Switzerland), 2018)
Stable antimicrobial nisin layers were prepared on the carrying medium-polyvinyl alcohol (PVA) films, crosslinked by glutaric acid. Surface plasma dielectric coplanar surface barrier discharge (DCSBD) modification of polyvinyl alcohol was used to improve the hydrophilic properties and to provide better adhesion of biologically active peptide-nisin to the polymer. The surface modification of films was studied in correlation to their cross-linking degree. Nisin was attached directly from the salt solution of the commercial product. In order to achieve a stable layer, the initial nisin concentration and the following release were investigated using chromatographic methods. The uniformity and stability of the layers was evaluated by means of zeta potential measurements, and for the surface changes of hydrophilic character, the water contact angle measurements were provided. The nisin long-term stability on the PVA films was confirmed by tricine polyacrylamide gel electrophoresis (SDS-PAGE) and by antimicrobial assay. It was found that PVA can serve as a suitable carrying medium for nisin with tunable properties by plasma treatment and crosslinking degree.
Keywords: plasma treatment polyvinyl alcohol; surface characterization; nisin; physical properties; antimicrobial film